Improving the performance of nadolol stereoisomers' preparative separation using Chiralpak IA by SMB chromatography - Arafah, Rami (2018)
The pseudobinary preparative separation of nadolol stereoisomers is performed by simulated moving bed chromatography (SMB). Using the Chiralpak IA adsorbent, a new 25:75:0.1 (v/v/v) methanol-acetonitrile-diethylamine solvent composition was selected to perform the experimental SMB separation and compare it with the previous results obtained using pure methanol. Using a 2 g L−1 total feed concentration of an equimolar mixture of the four stereoisomers of nadolol, the more retained component was fully recovered (100% purity and 100% recovery), with a system productivity of 0.77 g L−1 hour−1 and a solvent consumption of 9.62 L g−1. Comparing these results with the ones previously reported using 100:0.1 methanol-diethylamine solvent composition, this work shows that the 25:75:0.1 methanol-acetonitrile-diethylamine is a better alternative for the preparative separation of nadolol stereoisomers by SMB chromatography. These results are confirmed by simulation of the SMB operation for higher feed concentrations, by comparing the performances of the two solvent compositions using the data obtained experimentally through the measurement of the adsorption equilibrium isotherms and the kinetic data obtained for both solvents. The new experimental and simulation results stress out that the performance of the preparative separation can be improved by a careful selection of the solvent composition.